2020
DOI: 10.1177/1523422320907050
|View full text |Cite
|
Sign up to set email alerts
|

Vietnamese Women Entrepreneurs’ Motivations, Challenges, and Success Factors

Abstract: The Problem According to the Mastercard Index of Women Entrepreneurs, 31.3% of businesses in Vietnam are owned by women, placing Vietnam at the sixth out of the 53 surveyed economies. Despite the prevalence of female entrepreneurship in Vietnam, little is known about the motivations, challenges, and success factors of those occupying this vibrant sector of the Vietnamese economy. Greater knowledge of how women entrepreneurs perceive themselves and the Vietnamese business environment could stimulate greater sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 12 publications
1
15
0
1
Order By: Relevance
“…Women's career advancement opportunities are often blocked by marriages, childcare and the glass ceiling, which lead women to leave their jobs and start a business (Zgheib, 2018). When women have difficulties in maintaining work and life balance, they often decide to quit their jobs and start businesses (Nguyen et al, 2020). When downsizing occurs in organizations and there is a need to reduce work-family conflict, women choose self-employment (Agarwal and Lenka, 2015;Hughes, 2003).…”
Section: Push Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Women's career advancement opportunities are often blocked by marriages, childcare and the glass ceiling, which lead women to leave their jobs and start a business (Zgheib, 2018). When women have difficulties in maintaining work and life balance, they often decide to quit their jobs and start businesses (Nguyen et al, 2020). When downsizing occurs in organizations and there is a need to reduce work-family conflict, women choose self-employment (Agarwal and Lenka, 2015;Hughes, 2003).…”
Section: Push Factorsmentioning
confidence: 99%
“…Personal predictors for women's career success include their abilities and experiences, management skills and personality factors (Welsh et al, 2017). Nguyen et al (2020) indicated that expertize and experiences related to business start-up and independence and selfconfidence were the factors that resulted in women's success. O'Neil et al (2015) identified four essentials that contributed to women's career development, namely, self-confidence, self-efficacy, influence and authenticity.…”
Section: Career Successmentioning
confidence: 99%
“…(2013) found that, in Ukraine, women entrepreneurs did not receive substantial support from the government for entrepreneurship. Moreover, complex regulations, inaccessible government information and high-income taxes were among the challenges reported by Nguyen et al . (2020) for women entrepreneurs in Vietnam.…”
Section: Discussionmentioning
confidence: 99%
“…Iakovleva et al (2013) found that, in Ukraine, women entrepreneurs did not receive substantial support from the government for entrepreneurship. Moreover, complex regulations, inaccessible government information and high-income taxes were among the challenges reported by Nguyen et al (2020) for women entrepreneurs in Vietnam. Interestingly, Ozasir-Kacar and Essers (2021, p. 12) acknowledged that "the regulatory environment in Turkey for women entrepreneurs is supportive via prompt policies, yet biased and gendered with patriarchal norms and practices both in the private and public spheres".…”
Section: Discussionmentioning
confidence: 99%
“…Integrasi agama dan budaya di dalam komunitas lokal masyarakat yang dikombinasikan dengan kreativitas dalam membangun gagasan dan pendampingan kepada perempuan mampu menumbuhkan kepercayaan diri perempuan untuk keluar dari persepsi pragmatis patriarki dan membangun kemandirian ekonominya. Upaya-upaya ini secara kontekstual mampu merespon tantangan-tantangan yang selama ini dialamatkan kepada perempuan seperti, tantangan terkait hak-hak mereka: hak atas tanah dan aset (Akinola, 2018;Aluko, 2015;Folarin et al, 2014), tantangan di sektor informal (Peprah et al, 2019), tantangan dalam wirausaha perempuan (Nguyen et al, 2020;Saner & Yiu, 2019;Uddin, 2021) dan tantangan yang diterima oleh perempuan dalam berbagai bidang (Annes et al, 2021;Khan et al, 2018).…”
unclassified